A COMPARATIVE STUDY ON SHEIKH AZ-ZARNUJI THOUGHT AND IDEALISM IN THE PHILOSOPHY OF EDUCATION - M. Anas Thohir; Alfina C.; A. Dardiri (IAIN Tulungagung, 2017)
Textbooks Ta‘lîm al-muta‘allim can be an alternative solution to the problems of character education in Indonesia. Inside the book there are methods that specifically leads to holistic learning code like the concept of learning objectives, choose a teacher or school, choosing friends, even mastered a learning method such as learning itself, deliberation, mutharahah, and mudzakarah. This study aimed to analyze the text book Ta‘lîm al-muta‘allim works of Sheikh Az-Zarnuji then compare it with several books of Plato’s philosophy idealism. The method used is the analysis of documents by grouping clauses-clauses in the textbook Ta‘lîm al-muta‘allim in category: metaphysics, epistemology, axiology, the purpose of education, curriculum, method, the position of the students and teachers. Then compare it with documents from various sources about the Platoidealism. The study shows that there are some similarities between SheikhAz-Zarnuji thought with Plato. For example, the similarity between the two is the concept of metaphysics in Ta‘lîm al-muta‘allim called ma’rifatullah, while the concepts included in the Plato called the idealistic concept of macrocosm and microcosm. The similarity was impacted on shared educational goals from SheikhAz-Zarnuji, students and revitalize direction, into individual for himself, to achieve goodness and union with God. The difference mainly stated in the concept of metaphysics specific aspects in their respective reviews. For example, Sheikh Az-Zarnuji said that reality comes from God, while idealism states that the reality can be dug in God through contemplation or idea or reason.